More than our Differences: The Effects of Anticipated Diversity on Cognitive Performance. - Marotta, Satia. (2017)
Abstract: Research on the effect of diversity on performance suggests that in order to benefit from diversity, differences in knowledge, values, and social category must be synthesized. However, little is known about how our thinking may change when merely anticipating diversity in its simplest forms. This study assigned 132 participants to novel groups using the minimal group paradigm to ascertain potential differences in cognitive performance when participants anticipated interacting in either a homogeneous or diverse group. Results suggest that anticipating a diverse interaction may improve performance on some creativity and logical reasoning tasks, though findings were inconsistent across outcome measures. Anticipating diverse, as opposed to homogeneous, interactions may influence our cognitions about others and our performance on tasks in various and sometimes unanticipated ways.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Psychology.; Advisor: Samuel Sommers.; Committee: Evan Apfelbaum, and Keith Maddox.; Keyword: Social psychology.